Management of Indralupta (Alopecia areata) by Jaluka Avacharana and Shamana Aoushadhi: A Case Report - Rani, Pooja; Rathi, Mini; Chandrakar, Vinita; Tanwar, Vipin (International Research Journal of Ayurveda & Yoga, 2024)
Background: Alopecia areata is an autoimmune disorder that can lead to unpredictable hair loss. Alopecia areata is a common autoimmune disorder that often results in unpredictable hair loss. In most cases, hair falls out in small patches around the size of a quarter. There may be only a few patches, but alopecia areata can affect wider areas of the scalp. In Ayurveda texts, a similar condition is mentioned in Kshudrarogas known as Indralupta. Aims: This study sets out to evaluate the effectiveness of Shamana Aoushadhi and Jalaukavacharana in curing Alopecia areata. Materials and Methods: It is a single-case study of a 24-year-old female patient with a complaint of asymptomatic loss of hair at a single site over the scalp with itching and dandruff for 1.5 years. This case of Alopecia areata (Indralupta) was successfully treated with seven sittings of Jalaukavacharana (leech therapy) and Ayurveda medication. Result: The patch was immensely filled with lustrous black hairs at the end of the follow-up period. Conclusion: Thus, it can be said that Jaloukavacharana and Shamana Aushadh, two Ayurvedic treatments, offer a favorable outcome for Indralupta patients.